Portraying immediate postcolonial life of Jaffna- Theatrical representation of Dramatic Text of Prof.K.Kanapathippilai - Navadharshani, K. (University of Jaffna, 2015)
The Tamils has a long tradition of theatre performances in Sri Lanka. Kutu, Isainatakam, there are different genres and forms such as Koothu (Story depicted through a series of dances), Villasam (operatic aspects with prose forms), Isai Nadakam (operatic in style) and dialogue dramas. The dialogue dramas emerged during the 19th century onwards. In the 1930s Prof.K.Kanapathippilai (1903- 1958); linguistic and Tamil professor and the Head of the department of Tamil, University of Peradeniya from 1947 to 1965, started to write dialogue plays using colloquial Tamil language spoken in day to day life. This was a landmark attempt in the Tamil theatre history. And also his plays are theatrically, historically, socially, played significant role. Though he had not labeled as postcolonial play write, the works reflect the immediate postcolonial life of the indigenous. It a descriptive analysis based on the dramatic text of Pro.K.Kanapathippillai ‘Udaiyar Midduku’ (1940, the supremacy of Udayar). This study concentrates on the dramatic text in its context, understand the anatomy of the text and identify the historical importance of the play. As it is a dramatic text as well as historical document written and performs it is representation of portraying the immediate post-colonial Jaffna.
Keywords: Post-colonial theatre; Dramatic text and Theatrical representation